Islamic Etiquette for Slaughter viz a viz Mechanical Slaughtering - Dr Iman kanani (البصيرة, 2024)
Meat consumption has become the basic need of a human societies. According to Islamic Shariah, Allah the Creator, has allowed humans to consume the meat of halal animals and has stated a complete procedure of slaughtering the legally permitted animals. Adopting this process ensures the meat lawful for human consumption.  There are other methods and practices of slaughtering and killing animals followed by different people of different religions and thoughts. In the modern world various techniques are being used to kill animals on mass level in slaughterhouses. Gas chambers, electric current, rods and mechanical knives are used for this purpose. The users of these practices claim that these techniques make the slaughtering process easier and more convenient for the animal as compare to the shariah guided ways of slaughtering.